Evaluating the Effects of Yogic Training on Leg Strength and Cardio-Respiratory Endurance in University-Level Rugby and Volleyball Athletes. - Sashikanta Khuntia; Prof. (Dr.) Gaganendu Dash (Revista Electronica de Veterinaria, 2024)
Research looks at the impact of yogic training for leg strength and cardio-respiratory endurance among rugby and volleyball university players. Sixty athletes participated in a pre-experimental nonequivalent control group post-test design; the control group received only regular training, while the experimental group received additional training in structured yoga. Via pre-and post-intervention testing conducted over 12 consecutive weeks, several aspects of gain were determined, namely, the 1-RM leg press, vertical jump, VO2 max and the beep test. Positive statistical changes indeed observed in the intervention group in leg strength measure in both 1-RM leg press mean (I = 25.3 kg) and vertical jump mean (I = 4.5 cm) and cardio respiratory endurance with VO2 max mean increase (I = 3.4 ml/kg/min) and beep test levels mean increase (I = 1.3). These changes were found to be highly significant (p < 0.05) suggesting that yogic training improves the performance of athletes. Consequently, the inclusion of yoga training into athletes’ training schedules should be effective in preparing athletes for increased performances based on improved physical calisthenics crucial to highly specialized sports. This work joins the ever-growing chorus of voices stressing the need for coaches to incorporate yoga into traditional training methods for athletes.